The influence of community on relapse addiction to drug use : evidence from Malaysia. - Ibrahim, Fauziah; Kumar, Naresh (EuroJournals, 2009)
This paper presents findings on the relationship between community support and relapse addiction to drug use. 400 drug addicts on relapse cases were selected from eight drug rehabilitation centres throughout Peninsular Malaysia for the purpose of this study. The findings indicated that majority of the respondents perceived low to medium level of support from their community. Pearson correlation analyses indicated that there is a significant relationship between community support and relapsed addiction. The findings are consistent with previous research that community support is essential to mould good behaviour and to prevent relapsed addiction. Suggestions to curb relapsed addiction to drugs were discussed in relation to the findings.